PENGARUH TEKANAN WAKTU, INDEPENDENSI DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT DI KANTOR INSPEKTORAT KABUPATEN KEPULAUAN SANGIHE - Pikirang, Julita; Sabijono, Harijanto; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
This study aims to analyze the influence of time pressure, independence and auditor ethics on audit quality in Inspectorate Office of Sangihe Islands Regency. Data collection method used is with questionnaire technique with respondents who work in Inspectorate of Sangihe Islands Regency. Responspondents in this study amounted to 35. Data analysis techniques used were to use data quality test, classical assumption test and hypothesis test. Test the quality of data used is the test of validity and reliability test. The classical assumption test used in this research is normality test, multicolonierity test, and heteroscedasticity test. Hypothesis test used is multiple linear regression test and t test. The result of this research is time pressure and independence has no significant effect on audit quality while ethics has significant effect to audit quality. This means that the biggest influence on audit quality is ethics.Keywords: Time Pressure, Independence, Ethics and Audit Quality